2014
DOI: 10.4103/1947-2714.132936
|View full text |Cite
|
Sign up to set email alerts
|

Modified off-midline closure of pilonidal sinus disease

Abstract: Background:Numerous surgical procedures have been described for pilonidal sinus disease, but treatment failure and disease recurrence are frequent. Conventional off-midline flap closures have relatively favorable surgical outcomes, but relatively unfavorable cosmetic outcomes.Aim:The author reported outcomes of a new simplified off-midline technique for closure of the defect after complete excision of the sinus tracts.Patients and Methods:Two hundred patients of both sexes were enrolled for modified D-shaped e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Interestingly, wounds closed on the midline of the natal cleft took longer to heal compared with wounds closed off-midline, that may led to infection and other complication and previous studies showed recurrent cases. Recurrence of pilonidal sinus was the most commonly reported outcome by all the included studies [15].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, wounds closed on the midline of the natal cleft took longer to heal compared with wounds closed off-midline, that may led to infection and other complication and previous studies showed recurrent cases. Recurrence of pilonidal sinus was the most commonly reported outcome by all the included studies [15].…”
Section: Discussionmentioning
confidence: 98%
“…It is also important to note that recent literature on a variety of flap techniques, such as the Limberg flap or Karydakis flap, has been very promising with high rates of successful wound healing and low rates of reccurrence accompanying the application of these techniques [13]. However, such techniques are not without limitations [13][14][15]. It has been reported that flap techniques are associated with a high rate of postoperative pain as a result of flap mobilisation and multiple sutures [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that flap techniques are associated with a high rate of postoperative pain as a result of flap mobilisation and multiple sutures [13,15]. This can prolong inpatient length of stay, delay recovery and cause distress to the | 2965 patient [13,15]. Cosmetic outcomes can range from fair to poor based on the size and extent of reconstruction [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations